Why Has a Progressive Court Failed to Protect the Prison Population against COVID-19? Mass Incarceration and Brazil's Supreme Court - Daniel Wei Liang Wang; Luisa Moraes Abreu Ferreira; Paulo Sergio Coelho Filho; Matheus de Barros; Julia Abrahao Homsi; Mariana Morais Zambom; Ezequiel Fajreldines dos Santos (Harvard FXB Center for Health and Human Rights, 2023)
Despite acknowledging the risks of the COVID-19 pandemic for the prison population, Brazil's Supreme Court declined to issue structural injunctions during the health crisis ordering lower courts to consider these risks when making incarceration-related decisions. These injunctions could have been crucial to mitigate mass incarceration and protect the prison population during the pandemic. Through an examination of the Supreme Court's rulings in structural cases and in a sample of over 4,000 habeas corpus decisions, this paper argues that granting these injunctions would have overwhelmed the court with an unmanageable influx of individual claims. Consequently, the Supreme Court acted strategically in anticipation of its limited institutional capacity to enforce compliance with structural injunctions among lower courts. This case study illustrates how practical considerations can hinder structural decisions in criminal law and highlights the limits of structural litigation and constitutional jurisdiction to address mass incarceration.